Quantifying the benefits of liberalising trade in services - Organisation for Economic Co-operation and Development (Paris : Organisation for Economic Co-operation and Development, 2003)
What are the major barriers to services trade? To what extent would further liberalization of trade in services result in increased welfare gains and economic growth? It is critically important for governments to understand this if they are to participate effectively in, and maximize the benefits from, GATS negotiations. Empirical evidence is also important to demonstrate the economic effects of market and regulatory changes as an aid to the design of adequate regulatory reform.
The papers in this volume, presented at the Quantification Session of the Third OECD Services Experts Meeting, explore fundamental issues for empirical research on trade in services: How can methodologies for measuring the effects of restrictions be sharpened? How can modeling frameworks be improved to increase their relevance for negotiators and trade policy makers? How can the impact of regulatory reform in various services sectors be best captured in empirical models?
Ranging from economy-wide empirical assessments to sectoral research in telecommunications services, this volume provides information on available empirical research and highlights the specific data requirements and conceptual challenges for modeling liberalisation of services trade. It also identifies priority areas that will need to be addressed in order to increase the applicability of quantification work to the realities of the services economy and its potential use in a GATS context.
Papers from a conference, the Third OECD Services Experts Meeting, organized in conjunction with the World Bank in Paris in March 2002, under the chairmanship of Anders Ahlind
References : p. 169-171
Keywords: General Agreement on Trade in Services (Organization); Free trade; Service industries; International business enterprises